If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(p + 6q + -14) = 0 Reorder the terms: 3(-14 + p + 6q) = 0 (-14 * 3 + p * 3 + 6q * 3) = 0 (-42 + 3p + 18q) = 0 Solving -42 + 3p + 18q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 3p + 42 + 18q = 0 + 42 Reorder the terms: -42 + 42 + 3p + 18q = 0 + 42 Combine like terms: -42 + 42 = 0 0 + 3p + 18q = 0 + 42 3p + 18q = 0 + 42 Combine like terms: 0 + 42 = 42 3p + 18q = 42 Add '-18q' to each side of the equation. 3p + 18q + -18q = 42 + -18q Combine like terms: 18q + -18q = 0 3p + 0 = 42 + -18q 3p = 42 + -18q Divide each side by '3'. p = 14 + -6q Simplifying p = 14 + -6q
| 3x+8/5-7=-x+9 | | 7x+9=7(x+8) | | 4/0.8=0.3/w | | 0.50X+0.35(70)=36.5 | | 0.9/0.5=z/4.5 | | 2x^2-0=14 | | 45/50=m/100 | | x/7=8/21 | | (x-5)(x^2+2x+5)= | | 6y+2-8y=3-2y-10 | | =-2(7+6n) | | -4(x-1)-(2-x)=-6 | | -5/9y-(y-5/6)=1/54(y-6) | | 16x+8y=-17 | | 8n+10-2n=3n-2+5n | | 8n+10-22=3n-2+5n | | -2x-10=4+5x | | -3-2x=18 | | 8(3w-7)=6(4w+5) | | -15+2m=-11 | | 1/6(10x-3)=7 | | -5+2m=11 | | (x/3)+(4x+6) | | 5x^2-38x+21= | | -15+10= | | 12*x+2*x+2=352 | | 12*x+2*x+2=0 | | 9-a/a+5=a/a+5 | | 14x+2=0 | | -6x^2-216x-600=0 | | 7x^0= | | (x-5)(2x+2)= |